A study on the various factors which will impact the Motivation for the Employees in Small, Medium Scale Enterprises - N. Lakshmi Gayathri, Prasad Babu Jayanthi (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Employee Motivation is also one of the factor which will impact the performance of the employee and contribution of the employee towards the development of the organization. Motivated employees are an asset to an organization they are directly proportional to an organization’s success. Motivation is intangible, difficult to measure and extremely difficult to control, but very easy to facilitate if done right. It’s all about intention, intensity, and perseverance.In this paper the study of various factors like Employee motivation will impact the growth of the organization and contribution of the work towards the employee growth and organizational growth. Various samples are considered in Medchal, Telangana is studied and carried out for the purpose of understanding the HR and its policies and impact on SME’s.